Do Technology Shocks Lead to Productivity Slowdowns? : Evidence from Patent Data - Christiansen, Lone Engbo (IMF Working Papers; Working Paper ;, 2008)
This paper provides empirical evidence on the response of labor productivity to the arrival of new inventions. The benchmark measure of technological progress is given by data on patent applications in the U.S. over the period 1889-2002. The analysis shows that labor productivity may temporarily fall below trend after technological progress. However, the effects on productivity differ between the pre- and post-World War II periods. The pre-war period shows evidence of a productivity slowdown as a result of the arrival of new technology, whereas the post-World War II period does not. Positive effects of technology shocks tend to show up sooner in the productivity data in the later period.